Conceptual and political foundations for examining the interaction between nature and economy - Faber, Malte; Frick, Marc (Discussion paper series, 2019)
The aim of this paper is to contribute to an innovative agenda in the field of Environmental Economics. The paper focusses on a conceptual and political perspective on the interactions between nature and economy. Section 1 states that Environmental Economics has to consider three fields: nature, justice and the role of time. To operationalize this claim, we introduce fundamental concepts such as entropy, joint production, ignorance, evolution, absolute scarcity, responsibility and homo politicus and explain them in Section 2. These concepts are applied in Section 3 using a historical example, namely the soda-chlorine industry, extending over a period of about three centuries. The lessons taken from this economic, environmental and political evolution are outlined in Section 4. In Section 5, we apply the concept of responsibility to address political aspects dealt with when examining the interplay between nature and economy. In our outlook in Section 6, we argue that these concepts and further concepts do not form a hierarchically structured system. Instead they are conceived as a network of interdependent concepts that reference each other but also remain categorically distinct from one another.